Glacier systems and seasonal snow cover in six major Asian river basins: water storage properties under changing climate - Savoskul, Oxana S.; Smakhtin, Vladimir U. (International Water Management Institute, 2013)
This paper presents a comprehensive assessment of the water storage properties of glaciers and seasonal snow, carried out for the first time at a major river basin scale, for the Indus, Ganges, Brahmaputra, Amu Darya, Syr Darya and Mekong basins. It analyzes the changes of glaciers and snow under recent climate change, i.e., between the baseline (1961-1990) and current (2001-2010) periods. The paper also addresses climate change sensitivity of glacier systems and the changes that might be expected under a warming scenario for the end of the twenty-first century.